2002
DOI: 10.1897/1551-5028(2002)021<2483:aeraft>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Risk Assessment for Triclosan in Lotic Systems Following Discharge From Wastewater Treatment Plants in the United States

Abstract: A modeling study was conducted to examine the distribution of concentrations of the antimicrobial triclosan (2,4,4'-trichloro-2'-hydroxydiphenyl ether) in rivers following discharge from wastewater treatment plants (WWTPs). Most uses of triclosan are disposed of down residential drains and ultimately reach WWTPs. A modeling analysis was conducted to simulate the discharge of triclosan in WWTP effluents to rivers and calculate the expected concentrations based on characteristics of the reach where the discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 0 publications
2
49
1
1
Order By: Relevance
“…Both soils had similar K d values, with 17.6 L/kg and 17.8 L/kg for the sandy soil and the clay soil, respectively. The K OC values for the sandy soil and the clay soil were 1,958 L/kg and 939 L/kg, respectively, which were quite different from those reported by Reiss et al [21]. Since TCS has a p K a of 8.14, the majority of TCS in both soils is expected to be in a nonionic form.…”
Section: Resultscontrasting
confidence: 60%
“…Both soils had similar K d values, with 17.6 L/kg and 17.8 L/kg for the sandy soil and the clay soil, respectively. The K OC values for the sandy soil and the clay soil were 1,958 L/kg and 939 L/kg, respectively, which were quite different from those reported by Reiss et al [21]. Since TCS has a p K a of 8.14, the majority of TCS in both soils is expected to be in a nonionic form.…”
Section: Resultscontrasting
confidence: 60%
“…On the other hand, the value for triclosan is relatively high, ranging from 3.7 to 5.1, indicating that triclosan would be removed from the dissolved phase into sludge. A similar value (4.3) was determined for deactivated sludge (Reiss et al 2002). The K d values for triclosan in activated sludge from STP-2 was one order of magnitude higher than that from STP-1 (Table 3).…”
Section: Finland and Other European Countries (Paxé Us 2004)supporting
confidence: 74%
“…4,5 In animal experiments, low doses of TCS were ecotoxic to aquatic organisms and also had endocrine disrupting effects in amphibians and shes. [6][7][8][9] Furthermore, research has shown that TCS can cause DNA damage in human normal stem cells, and has an obvious time-effect relationship. 10 These studies concluded that risk assessments and toxicity information for TCS were signicant and urgently needed.…”
Section: Introductionmentioning
confidence: 99%